2004
DOI: 10.1128/ec.3.2.536-545.2004
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans Biofilms: a Developmental State Associated With Specific and Stable Gene Expression Patterns

Abstract: Like many bacteria, yeast species can form biofilms on several surfaces. Candida albicans colonizes the surfaces of catheters, prostheses, and epithelia, forming biofilms that are extremely resistant to antifungal drugs. We have used transcript profiling to investigate the specific properties of C. albicans biofilms. Biofilm and planktonic cultures produced under different conditions of nutrient flow, aerobiosis, or glucose concentration were compared by overall gene expression correlation. Correlation was muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
378
3
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(415 citation statements)
references
References 36 publications
28
378
3
6
Order By: Relevance
“…Many of the membrane proteins that undergo differential expression as a consequence of growth on agar are associated with the primary active transport of amino acids. To our knowledge there have been no previous connections proposed between either low-iron adaptation or biofilm formation and amino acid transport and metabolism, although amino acid starvation was identified as a trigger for biofilm formation for Candida albicans (Garcia-Sanchez et al, 2004). The induction of ABC transport systems which are not specific to amino acid transport has been reported as a consequence of biofilm formation (Pysz et al, 2004) although the functional relevance remains unclear.…”
Section: Growth Characteristicsmentioning
confidence: 99%
“…Many of the membrane proteins that undergo differential expression as a consequence of growth on agar are associated with the primary active transport of amino acids. To our knowledge there have been no previous connections proposed between either low-iron adaptation or biofilm formation and amino acid transport and metabolism, although amino acid starvation was identified as a trigger for biofilm formation for Candida albicans (Garcia-Sanchez et al, 2004). The induction of ABC transport systems which are not specific to amino acid transport has been reported as a consequence of biofilm formation (Pysz et al, 2004) although the functional relevance remains unclear.…”
Section: Growth Characteristicsmentioning
confidence: 99%
“…In the case of fungal biofilms, models used by different groups of investigators include the use of catheter disks, sheets and tubing from a variety of materials normally placed inside some type of sterile receptacle, glass and plastic slides, a perfused biofilm fermentor, microfermentors, cylindrical cellulose filters, acrylic strips and discs, germanium substratum, tissue culture flasks, syringes, modified Robbins devices, the Calgary biofilm device, the CDC reactor, etc., also including both biofilms formed under static and flow-through conditions [10][11][12][13][14][15][16][17][18][19][20][21] . Perhaps with the exception of the Calgary biofilm device, most of these models are complex, technically demanding and generally not amenable to high throughput screening since relatively few equivalent biofilms can be produced at the same time 6 .…”
Section: Introductionmentioning
confidence: 99%
“…However, Efg1 also regulates other genes that are not modulated by the cAMP pathway (Sohn et al, 2003;Doedt et al, 2004;Harcus et al, 2004;Setiadi et al, 2006). Numerous in vitro and in vivo studies with efg1 mutants have demonstrated that Efg1 is important for C. albicans virulence and for the interactions of C. albicans with endothelial and epithelia cells, as well as biofilm formation and catheter infection (Lo et al, 1997;Phan et al, 2000;Dieterich et al, 2002;Lewis et al, 2002;Ramage et al, 2002;Garcia-Sanchez et al, 2004). Despite its importance, molecular mechanisms for how Efg1 regulates gene expression during hyphal development and other processes are still unknown.…”
mentioning
confidence: 99%